Plugs, socket-outlets, vehicle connectors and vehicle inlets. Conductive charging of electric vehicles. Vehicle connector, vehicle inlet and cable assembly for DC charging intended to be used with a thermal management system Part 3-1, (31st March 2020) - British Standards Institution,
No abstract available